Gastric volvulus in a child with a diaphragmatic eventration: A case report - Samuel Amosilo Santoso Kesek; Alexandra Sachlan; Karina Priskila Setiawan (Elsevier, 2024)
Introduction: Pediatric gastric volvulus (GV) with diaphragmatic eventration is a rare but lethal condition. Case presentation: A 1-year-old girl complained of progressive vomiting, abdominal pain, and distension. On examination, plain abdominal radiograph demonstrated an air bubble sign in the left upper abdomen with elevation of the hemidiaphragm, while water-soluble contrast follow-through imaging showed partial gastric rotation. During exploratory laparotomy, gastric volvulus (GV) with left diaphragmatic eventration was identified. This abnormality was reduced by performing diaphragmatic plication and gastropexy. Postoperatively, the patient recovered without complications and was discharged on the tenth day of treatment. Conclusion: Pediatric gastric volvulus (GV) with diaphragmatic eventration is a surgical emergency. This case underscores the importance of considering GV in pediatric patients presenting with vomiting and abdominal symptoms, specifically when radiographic evidence suggests gastric distension and diaphragmatic abnormalities.